Wesley and the Anglicans: political division in early evangelicalism - Danker, Ryan Nicholas (IVP Academic, an imprint of InterVarsity Press, 2016)
Identity and challenge: defining early English evangelicalism -- Movement and conversion: Wesley in the trans-atlantic revival -- Propaganda and power: the revival under fire -- Politics and polity: Methodist structure and the question of dissent -- Enclaves and incursions: the geography of evangelicalism -- Eucharist and ethos: the formation of Methodist identity -- Hegemony and casualties: the Oxford expulsions of 1768 -- Vision and divergence: a new Anglican historiography -- Constrained to deviate